Marine Pollution in The Maritime Zones of Pakistan: A Green Theory Perspective - Baig, Noor ul Ain; Askari, Muhammad Usman (Annals of Human and Social Sciences, 2024)
Marine pollution poses a significant threat to the maritime zones of Pakistan which is adversely affecting the marine ecosystem and human well-being. This paper aims to examine the challenges associated with marine pollution in Pakistan’s maritime zones and propose strategies for countering its detrimental effects. The strategies to counter marine pollution in countries like Denmark, Norway, Indonesia, and South Africa have been discussed and how these strategies can be implemented in Pakistan. Data has been collected from primary and secondary sources. The discussion regarding countering marine pollution has been made under the theoretical lens of the green political theory, which adopts an eco-centric view instead of an anthropogenic view. To address the challenges faced due to marine pollution, this paper recommends using legislative measures, technological advancements, public awareness campaigns, and international cooperation. Enforcing stricter pollution control standards, and promoting sustainable practices in industries are important towards reducing pollution. Also, the adoption of advanced technologies for wastewater treatment and oil spill response, combined with regular monitoring and surveillance, can help to contribute to pollution prevention and control.